An overview of the abdomen - Kramer, Beverley (Henry Stewart Talks, 2022)
Boundaries and extent of the abdomen, Function of the abdominal cavity, Development of the gastrointestinal tract, Terminology of mesenteries, Components and organization of the abdominal cavity, including arrangements of viscera, Neurovascular supply